FACTORS AFFECTING PURCHASING DECISION OF USED – CAR IN RATCHABURI PROVINCE - Sangsawang, Thibordin; Surachotivet, Teeracahi; Muyha, Jiraporn; Phopuek, Natcha (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This research study the factors affecting the buying of used cars for customers in Ratchaburi province. The customers are divided according to income level. In this research, a sample group is sampling from customers of a local used car showroom. Questionnaires are used as a scaling research tool. The customers with the income levels of 10,001-15,000 baht are concerned with the price factor in terms of price which suitable car quality. Customers with income levels of 10,001-15,000 baht and 15,001-20,000 Baht focuses on product factors in terms of car size and brand. Customers with income levels less than or equal to 10,000 baht will pay more attention to marketing promotion factors in terms of car turnover service. The distribution channel factor is statistical test and found that the buyer group is not